Experience and thinking on collecting throat swab specimens in the nucleic acid testing clinic under the normalization of epidemic prevention and control of COVID-19 (新型冠状病毒肺炎疫情防控常态化下核酸检测门诊采集咽拭子标本的体会与思考) - ZHAO Jialu (赵佳璐); TANG Ling (唐玲); WANG Huaxin (王华新); WANG Xuesong (王雪送); XIAO Ruirui (肖锐锐) (Association of Integrative Nursing, 2022)
This paper summarized the process and methods of collecting throat swab specimens in the nucleic acid testing clinic under the normalization of epidemic prevention and control of COVID-19. Preparation of environment, goods and personnel was conducted according to the working standards before the sample collection. The collected samples were stored and transferred, and disposable protective clothing and equipments were removed according to regulations. The collection process, nurse management mode and sample transportation process were carried out in a well-organized and controlled way, and all collected samples were qualified for the test. No infection case reported in tested population and medical staffs. Improving the working environment of throat swab collection points and strengthening the protection and related training of throat swab operators are key issues in prevention of occupational exposure under the normalization of epidemic prevention and control of COVID-19. (本文对新型冠状病毒肺炎疫情防控常态化下核酸检测门诊采集咽拭子流程及方法进行总结。采集前按照操作规范进行环境、物品和人员准备, 采集后对样本进行保存转运并按规定脱防护服及用物处置。采集流程、护士管理模式、样本运送流程, 各项工作有序开展, 样本质量全部达标, 患者和医护人员"零"感染。改善咽拭子标本采集点的工作环境, 加强对咽拭子操作人员的保护和相关培训, 是预防职业暴露的重要环节。)